Sosialisasi Kearifan Lokal Masyarakat Baduy dalam Mitigasi Bencana di Perbatasan Wilayah Baduy - Permana, R. Cecep Eka; Nasution, Isman Pratama; Nugroho, Yogi Abdi; Putra, Hutomo (Paradigma: Jurnal Kajian Budaya, 2013)
The Baduy society has a local wisdom on disaster mitigation that many people outside the Baduy society are not aware of. Therefore, the Baduy community program is socializing the local wisdom to the people outside the community. The partnership of this effort is the youth of the elementary school to high school in the border area of the Baduy vicinity. In the beginning of the program, the students did not have any indication about the local wisdom of the Baduy people. However, after a period of lectures and discussions, their knowledge and understanding about the Baduy people and their wisdom on disaster mitigation have significantly increased.